Computer methods for stability analysis of the roesser type model of 2D continuous-discrete linear systems - Busłowicz, Mikołaj; Ruszewski, Andrzej (Zielona Góra: Uniwersytet Zielonogórski)
Asymptotic stability of models of 2D continuous-discrete linear systems is considered. Computer methods for investigation of the asymptotic stability of the Roesser type model are given. The methods require computation of eigenvalue-loci of complex matrices or evaluation of complex functions. The effectiveness of the stability tests is demonstrated on numerical examples.
Keywords: continuous-discrete systems; hybrid system; stability; computer methods